ANOMALY OF SERENTAK KEUCHIK ELECTION IN SUBULUSSALAM CITY 2017 (Teladan Baru Village, Rundeng Sub-District, Subulussalam City) - NUR HASANAH; Ubaidullah MA (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
ABSTRACTAnomalies in the simultaneous selection of the keuchik in the city of Subulussalam in 2017 were evident from the ineffectiveness of the keuchik selection process in Kampung Teladan Baru, Rundeng Sub-District, Subulussalam Municipality. The implementation of a good democracy is to cover every aspect of state life, starting with the election of the village head (keuchik). According to Qanun No. 4 of 2009 concerning the Election and Dismissal of the Keuchik in Aceh. Therefore the keuchik selection process was carried out, in accordance with the procedures for the election, but the selection process that was carried out had not proceeded properly.The writing of this thesis aims to explain the anomalies of keuchik selection in the New Kampung Teladan in Rundeng Sub-District, Subulussalam City, to explain why the community did not sue the implementation of keuchik elections.The method used in this study is library research and field researchers. Literature research was conducted to obtain secondary data by reviewing books and related scientific works, while field research was conducted to obtain primary data by interviewing respondents and informants.The results of this study indicate that the selection of keuchik in Kampung Teladan Baru, Rundeng Subdistrict, Subulussalam City was carried out once every 5 years and the keuchik was chosen by the people who were registered as voters. In the process of selecting keuchik in Kampung Teladan Baru, Rundeng Sub-District, Subulussalam City, the candidate papers were exchanged, and the absence of nails in the voting area at the time of voting. So in the selection of the keuchik in the New Kampung Teladan, Rundeng Subdistrict, Subulussalam City has not fully carried out the principles of democracy properly.It was suggested to the Kampung Teladan Baru keuchik selection committee in Rundeng Sub-District, Subulussalam City to be more responsible for the authority given to resolve the problem.Keywords: Anomalies, Keuchik Selection